Regulation of gene expression by retinoids - Amann, Philipp M.; Eichmüller, Stefan B.; Schmidt, Jan; Bazhin, Alexandr V. (Current topics in medicinal chemistry, 2011)
Vitamin A serves as substrate for the biosynthesis of several derivates (retinoids) which are important for cell growth and cell differentiation as well as for vision. Retinoic acid is the major physiologically active form of vitamin A regulating the expression of different genes. At present, hundreds of genes are known to be regulated by retinoic acid. This regulation is very complex and is, in turn, regulated on many levels. To date, two families of retinoid nuclear receptors have been identified: retinoic acid receptors and retinoid X receptors, which are members of the steroid hormone receptor superfamily of ligand-activated transcription factors. In order to regulate gene expression, all-trans retinal needs to be oxidized to retinoic acid. All-trans retinal, in turn, can be produced during oxidation of alltrans retinol or in a retinol-independent metabolic pathway through cleavage of β-carotene with all-trans retinal as an intermediate metabolite. Recently it has been shown that not only retinoic acid is an active form of vitamin A, but also that all-trans retinal can play an important role in gene regulation. In this review we comprehensively summarize recent literature on regulation of gene expression by retinoids, biochemistry of retinoid receptors, and molecular mechanisms of retinoid-mediated effects on gene regulation.